DETERMINAN KEJADIAN IBU HAMIL RESIKO TINGGI BERDASARKAN KARAKTERISTIK DI RUMAH SAKIT DAERAH SUBANG - Fitri Handayani; Wardah Fauziah (Jurnal Surya Muda, 2022)
Pregnancy and childbirth are natural (normal) processes not pathological processes, but normal conditions can become pathological. One of the main indicators of a country's health status is the Maternal Mortality Rate (MMR). This study aims to determine the determinant of the incidence of high-risk pregnant women based on the characteristics of the Subang district hospital. This study is a descriptive study, based on secondary data and primary data. The population in this study were all pregnant women in the third trimester who checked their pregnancy at the obstetric Poli Subang district hospital. The sample in this study were 143 pregnant women with high risk. Sampling technique used is perpusive sampling. Data analysis in this study using the chi square test. The results of this study obtained that there are still pregnant women have a high risk of 44.7 %, almost half of high-risk pregnant women are in the age category of 20-35 years as much as 37.1%, parity category that has a high risk in grandemultipara as much as 41.9% more than half of high-risk pregnant women occur in the category of not working as much as 53.1% while respondents with high school education category have a high risk pregnancy as much as 49.0%. All variables have a significant relationship to the incidence of high-risk pregnancy with p value < 0.05. This study is expected to be a material of knowledge about high-risk pregnancy and improve early detection in high-risk pregnant women, so as to reduce cases of maternal mortality.